Application of frequency ratio and logistic regression to active rock glacier occurrence in the Andes of San Juan, Argentina - Esper Angillieri, María Yanina (2010)
This study employs statistical modeling techniques and geomorphological mapping to analyze the distribution of active rock glaciers in relation to altitude, aspect, slope, lithology and solar radiation using optical remote sensing techniques with GIS. The study area includes a portion of the Dry Andes of the Cordillera Frontal of San Juan around 30°S latitude, where few geomorphological studies have been conducted. Over 155 rock glaciers have been identified, and 85 are considered active. The relationship between the variables and the rock glaciers distribution was analyzed using the frequency ratio method and logistic regression models. The analytical results show that elevations > 3824 m a.s.l., a south-facing or east-facing aspect, areas with relatively low solar radiation, and slope between 2° and 20° favor the existence of the rock glaciers, and demonstrate that lithology and slope exert major influences.